The Mental Effort-Reward Imbalances Model and Its Implications for Behaviour Management. Issue 2 (18th March 2016) - Poulton, Alison; Whale, Samina; Robinson, Joanne
Abstract : Attention deficit hyperactivity disorder (ADHD) is frequently associated with oppositional defiant disorder (ODD). The Mental Effort Reward Imbalances Model (MERIM) explains this observational association as follows: in ADHD a disproportionate level of mental effort is required for sustaining concentration for achievement; in ODD the subjective experience of reward for achievement is less than normal. In combination, these mechanisms predispose to reductions in motivation and achievement, and to low mood, oppositional behaviour, and reward seeking. Self-regulation has been used as a management strategy in ADHD, with interventions directed towards encouraging individuals to evaluate and reinforce positive behaviour. Using the logic of the MERIM, self-management strategies would be directed towards encouraging the individual to attribute value to a task or activity with the goal of obtaining the emotional outcome of feeling good about themselves through their achievement. We describe the use of two such strategies: positive rumination and positive reappraisal. These could potentially lead to improvements in functioning, enhancing the quality of life of affected individuals and resulting in fewer incidents of destructive, reward-seeking behaviour in relation to those around them.